LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENERIMAAN DIRI SISWA SMPN 3 CIMAHI - Nugraha, Novia Annisa; Wikanengsih; Rosita, Tita (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Self-acceptance is the basis for choosing and pursuing goals important for short-term and long-term happiness. The purpose of this research is to determine group guidance services to increase self-acceptance for class VIII students at SMPN 3 Cimahi. This research uses mixed methods or combination research. This research was conducted on 11 class VIII students who had a low self-acceptance category. Quantitative data was collected using a self-acceptance questionnaire with a total of 20 questions that had been validated with t-test results based on the output of Pair 1, which obtained a Sig value. (2-tailed) of 0.000 < 0.05, while qualitative data was collected using observation and interviews. The research results showed that the self-acceptance profile was in the medium category (76%) and using group guidance services to increase self-acceptance for class VIII students at SMPN 3 Cimahi. The results show that the group guidance service to increase self-acceptance for students at SMPN 3 Cimahi is effective for students in the low category to become the high category after receiving group guidance.